Analisis Frasa Verba dan Adjektiva pada Teks Cerpen dalam Buku Bahasa Indonesia Kelas IV SD Kurikulum Merdeka - Cholifia Nurchaliza; Nisreina Aura Kasih Nugraena; Pattriacia Roulina Br Malau; Rojwa Fadla Saniyya; Asep Purwo Yudi Utomo; Galih Suci Pratama (Pusat riset dan Inovasi Nasional, 2023)
The syntax is a grammar that can decipher the relationship of language elements to form sentences. The function of syntax is as a container in a syntactic structure that contains certain categories. It can be called subject (S), Predicate (P), Object (O), Complement (COMP), and Adverb (ADV). Phrase analysis in short story texts in Indonesian language books for fourth-grade elementary school independence curriculum. This analysis is a qualitative descriptive analysis of the short story text in the Indonesian language book for the fourth grade of the Independent Curriculum. Phrases are syntactic units cobining of two or more words and do not have clauses that occupy one function. Many do not understand how to divide groups of phrases and the causes of errors. Therefore, this research to classify phrases based on their types, and the causes of phrase errors in short stories texts in Indonesian language books for fourth-grade elementary school independence curriculum. Listening and then recording is a technique that can be done when data collection. The results of this study indicate that there are noun phrases, verb phrases, adjective phrases, numeral phrases, and errors in the use of phrases in short stories sentences. This analysis is expected to better understand and be able to develop the use of phrases in short stories.